Common Fixed Point Theorems Satisfying Contractive Type Conditions in Complex Valued Metric Spaces - Mahpeyker Öztürk (Abstract and Applied Analysis)
Some common fixed point theorems satisfying contractive conditions involving rational expressions and product for four mappings that satisfy property (E.A) along with weak compatibility of pairs are proved and further some results using (CLR)-property are obtained in complex valued metric spaces which generalize various results of ordinary metric spaces.